Non-Standard Channels of The Monetary Transmission Mechanism: Towards the Normalization Process - Aleksandra NOCOŃ (Communications of International Proceedings, 2022)
The paper undertakes very important aspects connected with the functioning of monetary transmission mechanism and its main channels, through which a central bank may impact on the financial sector as well as the real economy. The main aim of the study is to identify the most significant monetary transmission channels, providing their different classifications. Moreover, the article highlights the traditional channels, such as: interest rate channel, exchange rate channel and credit channel, but also pays particular attention to defining the unconventional monetary transmission channels, which were observed in the monetary transmission mechanism after the global financial crises. It also presents how the unconventional monetary transmission channels may be used in the process of modern monetary policy normalization. The paper revealed that the modern monetary transmission mechanism, supplemented by the new channels through which central banks impact on the different spheres, becomes an additional tool available for the monetary policymaker to control inflation expectations, cost of capital and undertaken risk.
Keywords: monetary transmission mechanism; monetary transmission channels; unconventional monetary transmission channels